2001
DOI: 10.1001/archpedi.155.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Removing the Pediatric Cervical Collar

Abstract: Discontinuing CSI without obtaining radiographs is common, especially among those with residency training in pediatrics and those in practice for less than 10 years. Knowledge of current practice is essential to future development of guidelines for managing pediatric trauma patients for whom cervical spine injury is a consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…33 A survey conducted before the publication of the NEXUS and CCR criteria found that physicians trained in either pediatrics or pediatric emergency medicine were twice as likely to clear a patient with a reassuring examination without using radiographs when compared with emergency medicine-trained physicians. 34 Overall, pediatric practice of clearing cervical spine injuries is highly variable among providers and institutions. 35 This variability in practice has led several institutions to develop cervical spine clearance protocols for children.…”
Section: Pediatric Cervical Spine Clearance Practicementioning
confidence: 99%
“…33 A survey conducted before the publication of the NEXUS and CCR criteria found that physicians trained in either pediatrics or pediatric emergency medicine were twice as likely to clear a patient with a reassuring examination without using radiographs when compared with emergency medicine-trained physicians. 34 Overall, pediatric practice of clearing cervical spine injuries is highly variable among providers and institutions. 35 This variability in practice has led several institutions to develop cervical spine clearance protocols for children.…”
Section: Pediatric Cervical Spine Clearance Practicementioning
confidence: 99%
“…The rate of clinical clearance was similar between general emergency physicians and pediatric emergency physicians. Our observed rate of self-reported clinical clearance, although approximate to a previously published self-reported clearance rate of 63%, 22 was surprising as it was our intent to create a clinical scenario of a young child for whom current guidelines recommend radiographic evaluation. 7,23 The unexpected rate of clinical clearance may be explained by several factors.…”
Section: Discussionmentioning
confidence: 44%
“…6 There was also no significant difference in terms of how often these groups use plain radiography or CT for investigating patients not cleared clinically. We had hypothesized that some physicians might go directly to CT to image the C-spine in those patients also requiring head imaging, yet 79% of respondents said that they ''almost never'' or only ''occasionally'' used CT under these circumstances.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the lack of clear guidelines, a survey of 1,360 physicians from the American Academy of Pediatrics and the American College of Emergency Physicians found that 63% of respondents reported that they would clear the C-spine of a 3-year-old comfortably without radiography. 6 Recognizing the need to provide guidance for physicians assessing potential C-spine injuries in patients less than 16 year of age, 8 of the 13 pediatric tertiary care hospitals in Canada have produced local guidelines (N.L.Y., unpublished data, 2006). This study revealed that of the physician groups sampled, at least half are using either locally modified adult guidelines or the most widely used adult tools (Canadian C-Spine Rules or NEXUS criteria) to clinically clear the C-spines of children of all ages, despite their not being valid for all ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation